Influence of the Cellular Ultrastructure and Enzyme Activity of the Leaf Sheath on Spontaneous Defoliation in Sugarcane - Xin Hu; Tiantian Wang; Shaochun Liu; Jiawen Guo; Jingmei Dao; Xinxin Gao; Rudan Li; Gaoyuan Liu (Tropical Plant Biology, 2024)
Spontaneous defoliation improves the harvesting efficiency and yield of sugarcane. Here, we investigated the ultrastructural changes and pectinase and cellulase activity in the third, fifth, and seventh leaf sheaths in four sugarcane varieties with varying spontaneous defoliation performance during maturation. At the early and middle stages of spontaneous defoliation, the cells in the abscission zones of the third, fifth, and seventh leaf sheaths were degrading. At the late stage, no complete organelles and hollow or broken spots in the cell walls were observed in the abscission zone cells of defoliation-prone varieties, while complete organelles and intact cell walls were present in the abscission zone cells at the same leaf positions in defoliation-resistant varieties. From the early to late stages, defoliation-prone varieties had higher pectinase activity in the abscission zones of the fifth and seventh leaf sheaths. At the early stage of defoliation, defoliation-prone varieties had significantly higher cellulase activity in the abscission zones of the third, fifth, and seventh leaf sheaths. Correlation analysis showed that the spontaneous defoliation rate was significantly positively correlated with pectinase activity in the leaf sheaths. In conclusion, the spontaneous defoliation of sugarcane was closely related to changes in cell morphology and pectinase activites in leaf sheaths.